The Strategic Role of Intercultural Education in Advancing the Internationalization of U.S. Higher Education - Mu, Qin (Research and Advances in Education, 2025)
Amidst the pervasive influence of globalization, the internationalization of higher education in the United States is imperative for maintaining its global educational preeminence. This study meticulously explores the pivotal role of intercultural education in catalyzing the internationalization of U.S. higher education. By integrating theoretical frameworks, empirical investigations, and case studies, an innovative intercultural education program is proposed, complemented by actionable policy recommendations. The study commences with a comprehensive review of intercultural education theories and the internationalization of higher education, constructing a robust theoretical framework that amalgamates intercultural psychology with educational principles. Subsequently, through the implementation of an intercultural education program at a U.S. university, the educational outcomes are systematically evaluated via questionnaires, student feedback, and teaching evaluations. The results unequivocally demonstrate that the intercultural education program markedly enhances students’ intercultural capabilities and the internationalization level of higher education, thereby providing substantial support for its advancement. Through case analysis, the study further substantiates the program’s effectiveness in practical applications and proposes policy recommendations to optimize intercultural education strategies in U.S. universities. The theoretical contribution lies in the introduction of an innovative intercultural education program, offering a novel perspective for intercultural education theory. In practical terms, the study provides empirical evidence of the program’s impact on enhancing the internationalization level of higher education, offering pragmatic solutions for U.S. universities.